Baypark Binondo a terminal, an elevated urban park, an office complex, a catalyst for the urban regeneration of Binondo - Julio, Wilford Jason G.; Chua, Johannes Vincent F. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Baypark Binondo is a catalyst project that will rejuvenate the Pasig River as a major thoroughfare for business and leisure, to create interest and foot traffic for buildings along the waterfront to be provided with the means to renovate its structure and facade to restore the historic image of the site.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Parks -- Design and construction